2012
DOI: 10.3892/ijmm.2012.894
|View full text |Cite
|
Sign up to set email alerts
|

miR-200b is involved in intestinal fibrosis of Crohn’s disease

Abstract: Intestinal fibrosis is one of the major serious complications of Crohn’s disease (CD). However, there are no effective antifibrotic drugs to treat intestinal fibrosis in CD. Therefore, it is important to understand the pathogenesis of fibrosis in CD. It has been reported that members of the miR-200 family are essential in the regulation of renal fibrogenesis. In this study, we analyzed the function of miR-200a and miR-200b in intestinal fibrosis, which was induced by transforming growth factor β1 (TGF-β1) in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…The study indicated that significant changes in miRNA expression are associated with the late-stage disease process. The miR-200 family has been shown to downregulate ZEB1/Zeb2 proteins, which are involved in fibrotic gene expression (47). Our data showed downregulation of miR-200b, miR-200b-5p, and 200b-3p miR-200a-3p, indicating higher expression of Zeb1/Zeb2 and increased fibrosis, in agreement with the previous report of Igietseme et al (44).…”
Section: Discussionsupporting
confidence: 92%
“…The study indicated that significant changes in miRNA expression are associated with the late-stage disease process. The miR-200 family has been shown to downregulate ZEB1/Zeb2 proteins, which are involved in fibrotic gene expression (47). Our data showed downregulation of miR-200b, miR-200b-5p, and 200b-3p miR-200a-3p, indicating higher expression of Zeb1/Zeb2 and increased fibrosis, in agreement with the previous report of Igietseme et al (44).…”
Section: Discussionsupporting
confidence: 92%
“…Intestinal fibrosis is a common serious complication of CD. In another study, they demonstrated that miR-200b could partially protect intestinal epithelial cells from fibrogenesis by suppressing EMT in vitro [60] . In summary, miR-200b played a potential role in maintaining intact of intestinal epithelium through inhibiting EMT and improving pathophysiology and clinical outcomes of IBD.…”
Section: Mirnas Regulate Intestinal Epithelial Barrier Functionmentioning
confidence: 98%
“…[15][16][17][18] Targeted analysis of isolated miRNA families has also shown the difference between nonstricturing CD (NSCD) and SCD patients. 12,19 Here, we perform the first comprehensive miRNA profiling of CD serum samples to distinguish between different CD phenotypes. We identify miRNAs in serum associated with SCD and validate the results in independent cohorts of CD patients.…”
mentioning
confidence: 99%